Calcipotriol Inhibits NLRP3 Signal Through YAP1 Activation to Alleviate Cholestatic Liver Injury and Fibrosis - Wang, Xiaopeng; Wang, Guiyang; Qu, Junwen; Yuan, Zhiqing; Pan, Ruogu; Li, Kewei (Frontiers in Pharmacology, 2020)
Cholestasis is a common disease with broad aetiologies. The NOD-like receptor protein 3 (NLRP3) pathway has been demonstrated to play an important role in liver injury and fibrosis induced by cholestasis. We previously proved that MCC950, a selective NLRP3 inhibitor, alleviates liver fibrosis and injury in experimental liver cholestasis induced by bile-duct ligation (BDL) in mice. Herein, we investigate the role of calcipotriol, a potent vitamin D receptor agonist, in experimental liver cholestasis, test its therapeutic efficacy, and explore its potential protective mechanism. C57BL/6 mice were made to undergo BDL or fed the 0.1% 3,5-diethoxycarbonyl-1,4-dihydrocollidine diet to establish two classic cholestatic models. Calcipotriol was administered intraperitoneally to these mice daily. Serum makers of liver damage and integrity, liver histological changes, levels of liver pro-fibrotic markers, bile acid synthetases and transporters, and the NLRP3 inflammasome and its downstream effectors were measured in vivo. The underlying mechanism by which calcipotriol alleviates cholestatic liver injury and fibrosis was further investigated in vitro. In conclusion, our findings proved that calcipotriol suppressed the NLRP3 signal by activating yes-associated protein 1 (YAP1) to alleviate liver injury and retard fibrogenesis in cholestasis.